Multiple Pleistocene refugia and repeated phylogeographic breaks in the southern Caspian Sea region: Insights from the freshwater crab Potamon ibericum. (10th April 2018) - Parvizi, Elaheh; Naderloo, Reza; Keikhosravi, Alireza; Solhjouy‐Fard, Samaneh; Schubart, Christoph D.
Abstract: Aim: Phylogeographic studies on a number of Western Palaearctic taxa imply that the southern Caspian Sea region served as a refugium during the Last Glacial Maximum (LGM). Nevertheless, the LGM biogeography of the terrestrial and freshwater organisms in this region is poorly understood. By studying phylogeography of a species of freshwater crab, we unravel the location of probable local refugia and colonization patterns across this topographically complex landscape. Location: Southern Caspian Sea region. Taxon: The freshwater crab Potamon ibericum . Methods: We inferred the demographic history of Potamon ibericum using 163 mtDNA Cox1 sequences from 16 localities. For a subset of specimens, we amplified mtDNA 16S and four nuclear markers (28S, Histone3, Enolase, NaK) to confirm the phylogeographic structure. We tested Pleistocene expansion–contraction dynamics, using species distribution modelling (SDM) and assessed morphological variability by geometric–morphometric methods. Results: Mitochondrial markers revealed the existence of three parapatrically distributed lineages in the western, central and eastern parts of the region. The more conserved nuclear markers did not reflect this. The SDM revealed the fundamental niche expansion of P. ibericum along the southern Caspian Sea during the LGM, agreeing with results from the Cox1 data of demographic expansions. Despite strong morphological resemblance, geometric–morphometrics elucidated clinal carapace shape variation. Main Conclusions: Considering the Caspian Sea level fluctuations during the late Pleistocene, we hypothesize a scenario of demographic contraction during interglacial/warmer conditions, due to the Caspian Sea transgression and latitudinal range shift within the narrow distribution of the species between the southern Caspian Sea and northern slopes of the Alborz Mountains. During the glacial periods, the sea regressed and moist and warm conditions, characterizing glacial refugia, became prevalent in the region and caused isolated populations to expand. Our study confirms the deep transverse phylogeographic break, previously identified for Darevskia lizards in the region, and adds support to the presence of several LGM refugia in the southern Caspian Sea region.